الوقاية من المخدرات بالمؤسسات التعليمية - حدد,عبدالرزاق; فرج الله,صورية (University of Eloued جامعة الوادي, 2023)
استهدف البحث التعرف على دور المدرسة في الوقاية من آفة المخدرات لدي التلاميذ واستخدم الباحث المنهج التجريبي وأنشأ نادي بالمتوسطة سمي نادي الوقاية من الآفات الاجتماعية متكون من 30 تلميذا ولغرض تحقيق أهداف البحث قدم الباحث برنامجا تعليميا متكاملا لمدة ستة اشهر , حيث قدم دروسا للتلاميذ, وعرض أشرطة وثائقية حول المخدرات والوقاية منها ,كما زار مركز معالجة الإدمان, ثم طلب من التلاميذ تقديم بحوث حول المخدرات, والقيام بحملات تحسيسية بالمؤسسة وتنشيط عرض مسرحي وورشة حول المخدرات وتقييم التلاميذ من خلال تقويم نهائي, حيث قدم التلاميذ اقتراحاتهم للوقاية من المخدرات, وتبين أنهم تبنوا فكرة الوقاية وأصبحوا أكثر وعيا من زملائهم الاخرين. abstract The research aimed to identify the role of the school in the prevention of drug pest among students and the researcher used the experimental approach and established a club in the middle called the club for the prevention of social pests consisting of 30 students For the purpose of achieving the objectives of the research, the researcher provided an integrated educational program of six months, where he provided lessons for students and presented documentaries about drugs and their prevention and visited the addiction treatment center and then asked the students to provide researches on drugs and carry out awareness campaigns in the school and do a theatrical show and a workshop on drugs and evaluate students through a final evaluation where students may suggest drug prevention and show that they adopted the idea of prevention and became more aware than their other colleagues.
دراسة ميدانية بنادي الوقاية من الآفات الاجتماعية بمتوسطة عياشي عمر نصر أم الزبد المقرن ولاية الوادي
Keywords: النوادي المدرسية; المؤسسات التربوية; المخدرات